An explosive condition: open cast coal mining soil subsurface biodiversity and the expression of nitrogen cycle genes (2010)
Open coal ANFO-cast pit mines present in the Guajira state are altered daily by anthropogenic activities. Detonation and removal of the earth's layers for the exposure of coal directly alters microbial ecology. Studying deep subsurface microbial ecology and the factors that influence it is a difficult task but seeing that the environment selects the microorganisms present in a particular place and time, the influence of the ANFO explosive was questioned. Two geographically separate pits were sampled, at three different distances from the surface with different times from the last detonation. Cultivable bacteria abundance, median and standard deviation, values show no statistically significant differences between both pits, while site location did influence plate count. Diversity indexes had the expected tendencies for most sites, except recently detonated locations. At the laboratory ANFO pressures were done to evaluate the influence of the explosive on the cultivated bacteria recovered from both mines. The pressure selected39% of total cultivable bacteria, 87.5% belonging to recently altered sites and 100%the identified individuals belonging to the Pseudomonas genus. RNA extraction of ANFO treatments as the only nitrogen and carbon sources available demonstrated the expression of narG, napA and nirS genes. Expression of nirS confirms 62.5% of the selected bacteria as denitrifiers. The ANFO explosive may explain the presence and abundance of the Pseudomonas genus in recently detonated sites, altering expected diversity index values. To conclude doubts about the effect of the explosive further studies centered on real time microcosm essays are needed to evaluate differential expression of denitrification genes, along with hydrocarbon degradation genes.